2008
DOI: 10.1016/j.jeconom.2008.09.017
|View full text |Cite
|
Sign up to set email alerts
|

High dimensional covariance matrix estimation using a factor model

Abstract: The variance-covariance matrix plays a central role in the inferential theories of high-dimensional factor models in finance and economics. Popular regularization methods of directly exploiting sparsity are not directly applicable to many financial problems. Classical methods of estimating the covariance matrices are based on the strict factor models, assuming independent idiosyncratic components. This assumption, however, is restrictive in practical applications. By assuming sparse error covariance matrix, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
447
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 589 publications
(455 citation statements)
references
References 45 publications
(53 reference statements)
4
447
0
4
Order By: Relevance
“…Multifactor models represent stock correlations using a small number of factors and thus significantly reduce the number of estimated parameters. Fan, Fan, and Lv (2008) showed that applying a factor structure to covariance matrix estimation is particularly advantageous when the covariance matrix is used for portfolio optimization.…”
Section: Cfapubsorg First Quarter 2018mentioning
confidence: 99%
“…Multifactor models represent stock correlations using a small number of factors and thus significantly reduce the number of estimated parameters. Fan, Fan, and Lv (2008) showed that applying a factor structure to covariance matrix estimation is particularly advantageous when the covariance matrix is used for portfolio optimization.…”
Section: Cfapubsorg First Quarter 2018mentioning
confidence: 99%
“…[7], [16]). In the financial domain, Fan et al [10] involve 3-factor model in the estimation of a covariance matrix. They find the factor model improves the estimation of the precision matrix, but affects errors in the estimation of the covariance matrix less.…”
Section: Introductionmentioning
confidence: 99%
“…There are several papers recently proposed in the literature to tackle this problem as, for example, Bickel and Levina (2008), Levina et al (2008), Fan et al (2008), Wang and Zou (2010), Bai and Shi (2011), Fan et al (2011), Fan et al (2012), Fan et al (2012a), Hautsch et al (2009), Fan et al (2013), and Lunde et al (2013) among many others. Our goal is to build an econometric methodology which will be used to construct dynamic models to forecast large covariance matrices estimated elsewhere.…”
Section: Introductionmentioning
confidence: 99%